Clinicopathological Correlation, Hematological Profile, and Risk Factor Assessment in patients Diagnosed with Endometrial Carcinoma. A Cross-Sectional Clinical Study - Summer Gul, Uzma Asif, Muhammad Tariq Hamayun Khan, Midhat Asif, Rooh Ali, Summan Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endometrial carcinoma is the most common gynecologic malignancy worldwide and is increasingly prevalent in developing countries like Pakistan. This malignancy is strongly associated with metabolic, hormonal, and lifestyle-related risk factors. Hematological parameters are emerging as accessible biomarkers for diagnosis, prognosis, and disease monitoring. Objective: To evaluate the clinicopathological characteristics, hematological profile, and risk factors in patients diagnosed with endometrial carcinoma at a tertiary care hospital in Peshawar, Pakistan. Methods: This cross-sectional study was conducted on 59 histologically confirmed cases of endometrial carcinoma at the Burns and Plastic Surgery Centre, Hayatabad Medical Complex, from July 2022 to March 2023. Clinical data were collected through structured interviews and hospital records. Hematological parameters including CBC, ESR, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were analyzed. Tumor characteristics were assessed histologically. Statistical analysis was performed using SPSS version 25, with p-values <0.05 considered significant. Results: The mean patient age was 57.3 ± 8.6 years, with 76.3% being postmenopausal. The most common presenting symptom was abnormal uterine bleeding (81.3%). Obesity (40.6%), diabetes (32.2%), and hypertension (35.6%) were the most prevalent comorbid conditions. Endometrioid adenocarcinoma was the dominant subtype (74.6%), and most tumors were Grade II (44.1%) and FIGO Stage I (61%). Deep myometrial invasion was noted in 33.9%, and lymphovascular space invasion in 28.8% of cases. Hematological analysis revealed anemia in 49.2%, thrombocytosis in 15.3%, and elevated ESR in 40.7%. Elevated NLR and PLR were significantly associated with higher tumor grade and LVSI (p < 0.05). Conclusion: Endometrial carcinoma in this cohort was strongly linked to metabolic risk factors and commonly presented at an early stage. Hematological markers such as NLR, PLR, and ESR may serve as supportive prognostic tools, especially in resource-limited settings. Integrating clinical, pathological, and hematological data can improve diagnostic accuracy and guide individualized treatment strategies. Keywords: Endometrial carcinoma, clinicopathological correlation, hematological profile, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio.